2017
DOI: 10.4028/www.scientific.net/ddf.377.189
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in a Non-Uniformly Heated Vertical Annular Cavity

Abstract: Natural convection from the linearly heated inner and/or outer walls of a vertical annular cavity has been numerically investigated. The bottom wall is uniformly heated and top cylindrical wall is thermally insulated. In this analysis, we considered two different thermal boundary conditions, namely case (I) and case (II) to understand the effect of non-uniform heating of inner and/or outer walls on the convective flow and subsequently the local and global heat transfer rate. For case (I), the inner and outer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Natural convection in porous media has applications in some engineering problems such as in cooling of MEMs, solar collectors, geothermal applications, building insulation materials and many others. Industrial application examples are given in [ 1 , 2 , 3 , 4 ]. In some industrial applications such as MEMs, coolers of nuclear reactors and many other magnetic field effects may be relevant [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection in porous media has applications in some engineering problems such as in cooling of MEMs, solar collectors, geothermal applications, building insulation materials and many others. Industrial application examples are given in [ 1 , 2 , 3 , 4 ]. In some industrial applications such as MEMs, coolers of nuclear reactors and many other magnetic field effects may be relevant [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Ri number was an important studied parameter. Other previous studies 11‐16 on convection over confined object entrenched in a square cavity have shown that the flow structure and thermal characteristics may depend on various factors such as the position of entry and exit ports, the induced velocity of buoyancy force, the position and number of obstacle cylinders, and fluid proprieties. Selimefendigil and Chamkha 17 investigated in three‐dimensional simulation the mixed convection of a nanofluid in a vented enclosure.…”
Section: Introductionmentioning
confidence: 98%
“…The enhancement of heat transfer has been the objective of many research articles in different applications such as discharge lamps [1][2][3][4][5][6][7][8][9][10][11]. In the same research area, many studies have been established to examine the natural convection heat transfer inside a porous medium due to the importance of this scientific research in many engineering applications, such as in solar collectors, the cooling of micro-electromechanical systems (MEMS) and various industrial applications, as reported by Pop and Ingham [12], Bejan et al [13], Vafai [14], Sankar et al [15] and Ben Hamida et al [16]. Chamkha and Selimefendigil [17] examined the generation of entropy and the natural convection inside a square corrugated cavity filled with porous medium saturated with nanofluid under the magnetic field effect.…”
Section: Introductionmentioning
confidence: 99%